Cas9-mediated knockout of Ndrg2 enhances the regenerative potential of dendritic cells for wound healing - Henn, Dominic; Zhao, Dehua; Sivaraj, Dharshan; Trotsyuk, Artem; Bonham, Clark Andrew; Fischer, Katharina S.; Kehl, Tim; Fehlmann, Tobias; Greco, Autumn H.; Kussie, Hudson C.; Moortgat Illouz, Sylvia E.; Padmanabhan, Jagannath; et al. (Nature Communications, 2023)
Chronic wounds impose a significant healthcare burden to a broad patient population. Cell-based therapies, while having shown benefits for the treatment of chronic wounds, have not yet achieved widespread adoption into clinical practice. We developed a CRISPR/Cas9 approach to precisely edit murine dendritic cells to enhance their therapeutic potential for healing chronic wounds. Using single-cell RNA sequencing of tolerogenic dendritic cells, we identified N-myc downregulated gene 2 (Ndrg2), which marks a specific population of dendritic cell progenitors, as a promising target for CRISPR knockout. Ndrg2-knockout alters the transcriptomic profile of dendritic cells and preserves an immature cell state with a strong pro-angiogenic and regenerative capacity. We then incorporated our CRISPR-based cell engineering within a therapeutic hydrogel for in vivo cell delivery and developed an effective translational approach for dendritic cell-based immunotherapy that accelerated healing of full-thickness wounds in both non-diabetic and diabetic mouse models. These findings could open the door to future clinical trials using safe gene editing in dendritic cells for treating various types of chronic wounds.